A credible homogenized finite element model to predict radius fracture in the case of a forward fall. (July 2022) - Revel, M.; Gardegaront, M.; Bermond, F.; Mitton, D.; Follet, H.
Abstract: Fragility fractures that occur after a fall from a standing height or less are almost always due to osteoporosis, which remains underdiagnosed and untreated. Patient-specific finite element (FE) models have been introduced to predict bone strength and strain. This approach, based on structure mechanics, is derived from Quantitative Computed Tomography (QCT), and element mechanical properties are computed from bone mineral densities. In this study, we developed a credible finite element model of the radius to discriminate low-trauma-fractured radii from non-fractured radii obtained experimentally. Thirty cadaveric radii were impacted with the same loading condition at 2 m/s, and experimental surface strain was retrieved by stereo-correlation in addition to failure loads in fracture cases. Finite element models of the distal radius were created from clinical computed tomography. Different density-elasticity relationships and failure criteria were tested. The strongest agreement (simulations-experiments) for average strain showed a Spearman's rank correlation (ρ) between 0.75 and 0.82, p < 0.0001, with a root mean square error between 0.14 and 0.19%. The experimental mean strain was 0.55%. Predicted failure load error (23%) was minimized for derived Pistoia's failure criterion. Numerical failure demonstrated area under the receiver operating characteristic (ROC) curves of 0.76 when classifying radius fractures with an accuracy of 82%. These results suggest that a credible FE modelling method in a large region of interest (distal radius) is a suitable technique to predict radius fractures after a forward fall. Graphical abstract: Image 1 Highlights: Homogenized finite element models (hFE) of the radius have been proposed to evaluate bone stiffness, strain and strength. Elastic-density relationships and failure criterion have an effect on numerical response on distal radius. hFE models of a large region of distal radius can be used to discriminate fractured bones from non-fractured bones.